From Old Labour to New Labour - Saadaoui, Halima (My University, 2017)
From old labour to new labour was pass for many phase .New Labour may be totally distinctive to of age Labour. It will additionally make fundamental with define history of the labour party .I will explain how the labour party begin ,first government and second government in chapter one .then , I was speaking in chapter two about origin ,Blair’s premiership , his legacy ,Tony Blair and Gordon Brown and competence between them .Finally, in chapter three I was speaking about the differences between old labour and new labour. New Labour was difficult for Tony Blair because it was conflict with Gordon Brown and who is received prime minister of British .
Keywords: Old labour; New labour; Tony Blair; Gordon Brown; Politics; History